Analysing Sukuk default cases: causes, remedies and regulatory implications - Azmi, Mohammad Shahid; Salleh, Safinar; Omoola, Sodiq; Hassan, Rusni (IIUM Press, 2025)
The growing significance of Sukuk as a Shariah-compliant financial instrument has been accompanied by a rise in default cases, highlighting critical financial, legal, and governance vulnerabilities. This article examines the principal causes of Sukuk defaults, including inefficient liquidity management, regulatory inconsistencies, and governance deficiencies, as evidenced in the cases of Menara ABS Berhad, MEX II Sdn Bhd, and Serba Dinamik Holdings Berhad. Distinguishing between asset-backed and asset-based Sukuk is crucial for understanding investor risk exposure, especially in relation to ownership rights and bankruptcy protections. Legal uncertainties, jurisdictional conflicts, and ineffective enforcement measures exacerbate challenges in resolving defaults. This study employs a qualitative methodology, combining doctrinal and empirical analyses to explore regulatory deficiencies and suggest reforms. The findings emphasise the need for stronger governance, harmonised legal frameworks, and proactive risk management strategies to strengthen the Sukuk market against default risks, thereby ensuring its sustainability within the global Islamic finance ecosystem.